Study on Hyaluronic Acid and Its Applications in Cosmetics - Zhang, Pingyu (Transactions on Environment, Energy and Earth Sciences, 2026)
This paper examines the role of hyaluronic acid (HA) in cosmetics, focusing on the challenges of rapid degradation and limited penetration that reduce its effectiveness. The purpose of the paper is to evaluate how molecular weight and formulation design influence the stability of HA and their performance. Specifically, it investigates how adjusting the range of molecular weight could affect HA’s ability to act on different skin layers, meanwhile focus on optimized formulations address its inherent instability issues. Recent research was included to compare conventional HA with modified approaches such as nano-carriers and cross-linked hydrogels. Evidence shows that these modified systems prolong hydration time, enhance skin barrier recovery, and improve the stability of HA structure. For example, employment of nano-carriers promotes deeper epidermal penetration, whereas cross-linked hydrogels form robust polymeric networks that resist enzymatic degradation. Collectively, these findings suggest that HA is transitioning from a short-term moisturizer to a multifunctional ingredient with a wide range of potential uses in cosmetics.